Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s11999-012-2610-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-functionalized Dextran Nanosystems to Overcome Multidrug Resistance in Cancer: A Pilot Study

Abstract: Background The toxicity of anticancer agents and the difficulty in delivering drugs selectively to tumor cells pose a challenge in overcoming multidrug resistance (MDR). Recently, nanotechnology has emerged as a powerful tool in addressing some of the barriers to drug delivery, including MDR in cancer, by utilizing alternate routes of cellular entry and targeted delivery of drugs and genes. However, it is unclear whether doxorubicin (Dox) can be delivered by nanotechnologic approaches. Questions/Purposes We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 50 publications
1
26
0
1
Order By: Relevance
“…Our group and others have previously shown that dextran-based nanoparticles are able to efficiently deliver both the chemotherapy drug doxorubicin as well as siRNA to osteosarcoma cells with no apparent toxicity. [31][32][33]37 We also previously found that dextran-based nanoparticles can efficiently transport siRNA into tumor cells. 32,33 More recently, cationized dextran nanoparticles encapsulated with C-X-C chemokine receptor type 4 (CXCR4) siRNA have been shown to significantly downregulate CXCR4 expression in colorectal cancer, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our group and others have previously shown that dextran-based nanoparticles are able to efficiently deliver both the chemotherapy drug doxorubicin as well as siRNA to osteosarcoma cells with no apparent toxicity. [31][32][33]37 We also previously found that dextran-based nanoparticles can efficiently transport siRNA into tumor cells. 32,33 More recently, cationized dextran nanoparticles encapsulated with C-X-C chemokine receptor type 4 (CXCR4) siRNA have been shown to significantly downregulate CXCR4 expression in colorectal cancer, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…32,33 Briefly, a stock solution of 5 mg/mL (~2.5 mM) dextran thiol, 5 mg/mL (~2.5 mM) dextran hexylamine, 5 mg/mL (125 µM) PEG-thiol, and 2 µM miR solution was prepared. For obtaining a 100 nM miR concentration, a 120 µL stock solution of miR was mixed with 40 µL of dextran-thiol stock solution using a vortex shaker.…”
Section: Encapsulation Of Micrornas In Functionalized Dextran-based Nmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP mediated efflux pumps is one of the most well studied mechanism of MDR and several therapeutic strategies using small molecules and biologics have been used to overcome this resistance (43,44). However drug resistance attributed to activation of antiapoptotic cellular defense is also known to lead to drug resistance.…”
Section: Overcoming Mdr By Modulating Apoptotic Genes and Proteinsmentioning
confidence: 99%
“…Kobayashi et al extended the application of dextran nanoparticles for the delivery of siRNA by loading MDR1 siRNA in octylamine-modified dextran, dextran-PEG, and dextran thiol (44). The nanoparticles were in the size range of 101±3 nm with a zeta potential of −0.22 mV.…”
Section: Oligonucleotides (Sirna/microrna)mentioning
confidence: 99%